PENGARUH KEPEMILIKAN PEMERINTAH DAN KOMITE AUDIT TERHADAP PENGHINDARAN PAJAK DENGAN KUALITAS AUDIT SEBAGAI PEMODERASI - Zulfa Rizqiyah Asshafi (2023)
This study is to empirically prove the impact of government ownership, audit committees, and audit quality on tax avoidance practices, as well as prove the role of audit quality moderation on the impact of government ownership and audit committees on tax avoidance practices. This study estimates tax avoidance with accounting ETR, audit committee with a comparison of members who have accounting or financial science fields to the number of all members, and audit quality with audit fees. This study selected samples using purposive sampling and produced 11 private energy sector companies and 9 non-financial SOEs that IPO on the IDX in the 2016-2021 period to be used as samples. This study used the GLS method and found that: (1) government ownership and audit committees had no effect on tax avoidance practices; (2) audit quality negatively affects tax avoidance practices; (3) audit quality weakens the influence of government ownership on tax avoidance practices; and (4) audit quality cannot moderate the audit committee towards tax avoidance practices.